First record of the genus Ficobracon (Hymenoptera:Braconidae) from India, with description of new species - Maqbool, Amir; Akbar, Shahid Ali; Wachkoo, Aijaz Ahmad (Zootaxa, 2018)
Ficobracon kashmirensis sp. nov., a new braconid species from Kashmir Himalayas, India, is described with illustrations. The discovery marks the first record of Ficobracon from India, and is the fifth known species of the genus globally. A discussion on the seasonal occurrence and some elements of biology, together with a revised key to the known species, are also provided.